Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1158/1078-0432.ccr-10-0173
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-27 Acts as Multifunctional Antitumor Agent in Multiple Myeloma

Abstract: Purpose: Multiple myeloma (MM) derives from plasmablast/plasma cells that accumulate in the bone marrow. Different microenvironmental factors may promote metastatic dissemination especially to the skeleton, causing bone destruction. The balance between osteoclast and osteoblast activity represents a critical issue in bone remodeling. Thus, we investigated whether interluekin-27 (IL-27) may function as an antitumor agent by acting directly on MM cells and/or on osteoclasts/osteoblasts.Experimental Design: The I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 51 publications
2
90
0
Order By: Relevance
“…[146][147][148] Similarly to IL-12, IL-27 has been shown to inhibit tumor growth and metastasis. 149 The mechanisms that drive IL-27 antitumor effects include inhibition of angiogenesis [150][151][152] and tumor cell proliferation, 153,154 and the activation of CD8 þ T and NK cells. 155,156 As IL-27 acts only on naive T cells, the concentrations of IL-27-induced pro-inflammatory cytokines are presumably not high enough to induce the appearance of adverse side effects.…”
Section: Mechanisms Of Tumor Protection Through Il-12mentioning
confidence: 99%
“…[146][147][148] Similarly to IL-12, IL-27 has been shown to inhibit tumor growth and metastasis. 149 The mechanisms that drive IL-27 antitumor effects include inhibition of angiogenesis [150][151][152] and tumor cell proliferation, 153,154 and the activation of CD8 þ T and NK cells. 155,156 As IL-27 acts only on naive T cells, the concentrations of IL-27-induced pro-inflammatory cytokines are presumably not high enough to induce the appearance of adverse side effects.…”
Section: Mechanisms Of Tumor Protection Through Il-12mentioning
confidence: 99%
“…Interestingly, IL-27 exerts opposing effects in comparison to IL-3 and IL-7. This cytokine has anti-tumor, anti-angiogenic and anabolic effect in MM, and therefore may represent a promising therapeutic agent [74].…”
Section: Pathogenesis Of Osteoblast Inhibition In MMmentioning
confidence: 99%
“…7,8 IL-27 exerts antitumor activity in different tumors through indirect 5,9-11 and direct mechanisms. 12,13 Furthermore, functional screenings of genes expressed in acute myeloid leukemia cells revealed that the IL-27R possesses hematopoietic cell-transforming properties, 14 but no information is available on the role of IL-27/IL-27R in pediatric acute lymphoblastic leukemias.…”
Section: Introductionmentioning
confidence: 99%